2023
DOI: 10.3389/fbioe.2023.1163057
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of heavy metals in the conversion of lake sediment and restaurant waste by black soldier fly (Hermetia illucens)

Abstract: The risk posed by heavy metals makes it difficult to dispose of sediment contaminants from dredging lakes in China. Black soldier fly (Hermetia illucens) can convert organic waste, such as restaurant waste and lake sediment, to high-value-added protein feed and fertilizer. Experimental groups were formed in this study to explore the conversion of heavy metals present in the mixture of restaurant waste and lake sediment by black soldier fly larvae (BSFL). The results demonstrated that BSFL could survive in pure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…By contrast, although the digestate contained a higher concentration of heavy metals than the food waste, the accumulation in the larvae did not exceed the limits, making it a potentially suitable feed for larvae for future use. Our findings align with similar studies for various food waste [ 54 , 66 , 67 , 68 , 69 , 70 ], where the levels of Pb in larvae for food waste range from 0.08 to 1.5 mg/kg, while Cd ranges from 0.02 to 7.9 mg/kg, and Cr ranges from 0.08 to 3 mg/kg. Previous studies have shown that Cd and Pb can accumulate in larvae [ 18 , 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…By contrast, although the digestate contained a higher concentration of heavy metals than the food waste, the accumulation in the larvae did not exceed the limits, making it a potentially suitable feed for larvae for future use. Our findings align with similar studies for various food waste [ 54 , 66 , 67 , 68 , 69 , 70 ], where the levels of Pb in larvae for food waste range from 0.08 to 1.5 mg/kg, while Cd ranges from 0.02 to 7.9 mg/kg, and Cr ranges from 0.08 to 3 mg/kg. Previous studies have shown that Cd and Pb can accumulate in larvae [ 18 , 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…BSFL do bioaccumulate heavy metals and other elements depending on what is present in the feed, meaning some studies find no bioaccumulation of certain elements that other studies do. The bioaccumulation factors for cadmium and manganese are consistently the highest, followed by arsenic, lead, iron, zinc, mercury, copper, chromium, magnesium, potassium, and tin; these factors are consistently below 1 (no bioaccumulation) for aluminum, cobalt, molybdenum, nickel, selenium, silver, or vanadium [ 6 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. While this could reduce the suitability of the insects for use in feed, it does serve to decontaminate the substrate and produce a cleaner residue for downstream uses [ 8 , 54 , 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…The bioaccumulation factors for cadmium and manganese are consistently the highest, followed by arsenic, lead, iron, zinc, mercury, copper, chromium, magnesium, potassium, and tin; these factors are consistently below 1 (no bioaccumulation) for aluminum, cobalt, molybdenum, nickel, selenium, silver, or vanadium [ 6 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. While this could reduce the suitability of the insects for use in feed, it does serve to decontaminate the substrate and produce a cleaner residue for downstream uses [ 8 , 54 , 57 ]. Some evidence suggests heavy metal contamination negatively affects the natural BSFL gut microbiome and leads to the enrichment of pathogens in the gut [ 56 , 59 ].…”
Section: Introductionmentioning
confidence: 99%